Higher education enrollment by area of knowledge and regions in México 2010-2022 - Arroyo Arroyo, Ignacio; Vázquez Olarra, Glafira; Hernández Oceguera, Eva Angelina (Emerging Trends in Education, 2024)
The objective of the research is to describe the behavior of enrollment in Mexico from the school year 2010-2011 to 2021-2022 divided by area of knowledge in the eight regions of the country. A quantitative approach was used, with a non-experimental type and an exploratory-descriptive scope in an evolutionary way, taking information from the ANUIES about public higher education institutions, and schooling modality. Throughout the country, from the 2010-2011 cycle there was an enrollment were 1,933,907 to 2021-2022 with 3,493,562 students. The areas with the highest enrollment are Engineering, Manufacturing and Construction; Social Sciences and Law; along with Administration and Business. In the last twelve years, enrollment in Mexico has increased by 44.64%; being the area of Services the one that grew the most with 63.94% along with that of Natural Sciences, Mathematics and Statistics with 58.7%. The one that had a decrease was the Area of Education Sciences with -52.24%; and Information and Communication Sciences with just 5.12% growth. In the last school year 2021-2022 with respect to the previous one; the ones that grew the most were Education Sciences (10.49%) and Information and Communication Technologies (12.23%).
Keywords: Higher education; public institutions; school enrolment; México; regions